2002
DOI: 10.1139/t01-080
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between laboratory and in situ values of the coefficient of primary consolidation cv

Abstract: Many curve-fitting procedures based on the Terzaghi uncoupled consolidation theory have been proposed for the determination of the laboratory coefficient of primary consolidation, cv. This paper presents data from ten oedometer tests performed on clay samples from three different sites, with the cv values having been obtained using four different fitting procedures.The in situ settlements of the clay layers were measured using borehole extensometers. In this way the in situ cv values of the same clay tested in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…When going deeper, the cohesion increased steadily (Figs 7 and 8). A similar picture may be seen on the graphs of h ϕ − relationship which indicate the same depth of 2 m and 2.5 m. It was assumed that at the indicated depths clay structure was already damaged and the slope would slip along the surface located at this depth in the near future (Cortellazzo 2002). Actually, the slip happened on the site in the following spring after our investigations.…”
Section: Some Characteristics Of Clay Mechanical Propertiessupporting
confidence: 80%
“…When going deeper, the cohesion increased steadily (Figs 7 and 8). A similar picture may be seen on the graphs of h ϕ − relationship which indicate the same depth of 2 m and 2.5 m. It was assumed that at the indicated depths clay structure was already damaged and the slope would slip along the surface located at this depth in the near future (Cortellazzo 2002). Actually, the slip happened on the site in the following spring after our investigations.…”
Section: Some Characteristics Of Clay Mechanical Propertiessupporting
confidence: 80%
“…The issue with the remaining methods at D/H less than 2.5 especially at D/H 0.5 was that the secondary consolidation was not clearly observed rendering difficulty in deriving c v from curve fitting procedure. Previous researcher's showed that c v obtained using Taylor's method is higher than that attained using Casagrande method and Inflection method gives quite a similar result to that of Casagrande method [2,12,20,23]. The reason being; Taylor's method is affected by the initial compression (leading to an increase in c v ) and in some cases secondary compression (decrease in c v value).…”
Section: Effect Of D/h Ratio On the Ratio Of [C V (√T) / C V (Log T)]mentioning
confidence: 72%
“…The response of Cv to pressure increase in clays is governed by the mechanical and physicochemical factors that govern the compressibility [23]. The comparison between in situ and laboratory Cv values show that the macrostructure of the soil layer influences the behavior of the whole layer [24]. For soils that are overconsolidated, base the classification on Cr/(1+eo) Figure 12.…”
Section: Compression Characteristics Of Sabak Bernam Marine Claymentioning
confidence: 99%